Men in the nursery gender and caring work - Cameron, Claire; Moss, Peter, 1945-; Owen, Charlie; Sage eBooks (London : Paul Chapman, 1999)
Men in the Nursery is an examination of the issues surrounding gender and childcare. 99% of childcare workers are women. This text considers the case for employing more men and what steps might be taken to achieve this.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Male child care workers -- Great Britain; Sex role in the work environment -- Great Britain; Child care services -- Great Britain; Child care workers -- Great Britain; Electronic books